JURNAL ILMIAH TAK PENTING: KONTROVERSI PENERBITAN JURNAL SENI DAN DESAIN - H Istanto, Freddy (Nirmana, 2002)
There have been several controversies on the management and publication of scientific journal in the scope of arts and designs. Scientific trial and application can be presented through these articles. Nevertheless, most of them who deals in arts and designs would prefer to devote their skills to enhance their practiced quality rather than the theoretical. Several approaches on journal s management and publication have been issued in order to motivate its continual (constant) publication. Some classical but significant aspects still appear to restrain this continuity, for example financial, operational, administration and management. Yet, the major obstacle is the lack of people s interest to write. Abstract in Bahasa Indonesia : Pengelolaan dan penerbitan jurnal ilmiah di lingkup seni dan desain menghadirkan beberapa kontroversi. Lewat artikel-artikel ilmiah pengujian dan aplikasi keilmuan dapat dihadirkan. Namun banyak dari mereka yang bergelut di bidang seni dan desain, lebih memilih berkarya (seni dan desain) untuk meningkatkan kualitas dirinya dibandingkan berolahtulis. Beberapa pendekatan-pendekatan dipaparkan dalam pengelolaan dan penerbitan jurnal agar sebuah jurnal di lingkup seni dan desain dapat secara ajeg terbit. Aspek-aspek klasik seperti pendanaan, operasional administrasi dan manajemen tetap menjadi masalah. Problematika utama adalah pengadaan artikel yang sangat sulit diharapkan. scientific journal, controversies, the management of the arts and designs journal.